2021
DOI: 10.3390/insects12121082
|View full text |Cite
|
Sign up to set email alerts
|

Feed and Host Genetics Drive Microbiome Diversity with Resultant Consequences for Production Traits in Mass-Reared Black Soldier Fly (Hermetia illucens) Larvae

Abstract: Mass rearing the black soldier fly, Hermetia illucens, for waste bioremediation and valorisation is gaining traction on a global scale. While the health and productivity of this species are underpinned by associations with microbial taxa, little is known about the factors that govern gut microbiome assembly, function, and contributions towards host phenotypic development in actively feeding larvae. In the present study, a 16S rDNA gene sequencing approach applied to a study system incorporating both feed subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 116 publications
(148 reference statements)
2
14
0
Order By: Relevance
“…Although diet can have only limited effects on altering BSFL core microbiota [ 100 ], most previous reports documented strong diet-related microbial dynamics [ 101 , 102 , 103 , 104 ]. Particularly population variation is interesting [ 105 ], and a recent study [ 106 ] supports that the G×E interactions for several relevant traits observed here may reflect even more complex interactions involving associated microbes. Identifying beneficial cultivable or transmittable microbial candidates depends on their characteristics and the nature of their host association.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although diet can have only limited effects on altering BSFL core microbiota [ 100 ], most previous reports documented strong diet-related microbial dynamics [ 101 , 102 , 103 , 104 ]. Particularly population variation is interesting [ 105 ], and a recent study [ 106 ] supports that the G×E interactions for several relevant traits observed here may reflect even more complex interactions involving associated microbes. Identifying beneficial cultivable or transmittable microbial candidates depends on their characteristics and the nature of their host association.…”
Section: Discussionmentioning
confidence: 59%
“…Hence, genetic variation across strains is not unexpected. Accordingly, the pervasive influence of an additional interaction level involving systemically relevant microbes exhibiting more or less tight host associations cannot be ruled out for the BSF [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first publications on this aspect appeared in the last few years (e.g. Greenwood et al, 2021;Jiang et al, 2019;Klammsteiner et al, 2021;Kooienga et al, 2020;Tegtmeier et al, 2021;Yang et al, 2021;Zhang et al, 2021), but likely they have uncovered only the top of the iceberg of possible roles that microorganisms can have in the BSF larval gut. For instance, while it may be tempting as a first step to make predictions or draw conclusions on functions of specific genera (metabolic phenotypes, for instance determined by Greenwood et al (2021) and Yang et al (2021)) based on their abundance in different substrates, Klammsteiner et al (2021) noticed that shifts in diets induce clear shifts in the microbiome composition, but they do not modify the main metabolic pathways, as they remain relatively stable.…”
Section: Introductionmentioning
confidence: 99%
“…Although the bioproductive implications of some biologically active compounds and their impact on the quality of animal products and by-products require further studies [ 27 , 28 , 29 , 30 ], all these authors recommend the use of H. illucens protein meal and oil in the diet of farmed species [ 31 , 32 , 33 , 34 , 35 , 36 ]. Some qualitative shortcomings of H. illucens protein meal and oil can be overcome by manipulating the structure of the larval growth substrate, which can significantly change the nutrient composition of the larvae [ 37 , 38 , 39 , 40 ]. The species also offers promising opportunities regarding the use of H. illucens oil in the cosmetics industry [ 41 , 42 ], or as a potential source of fuel, biodiesel, respectively [ 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%